Pelatihan Stimulasi dan Deteksi Perkembangan Balita Menggunakan KPSP Pada Kader Posyandu - Luluk Alfiya; Ishaq Syahid (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2024)
The important period in child development is at the age of under five years because at that age it influences and determines the child's further development. Early stimulation itself is a stimulation that is carried out since being in the womb, carried out every day, to stimulate all sensory systems from hearing, sight, touch, smell, taste. During this toddler period, the development of language skills, creativity, social awareness, emotional and intelligence runs very quickly as the foundation for subsequent development, so that any abnormalities or deviations, no matter how small, if not detected and not handled properly. Children who receive targeted and regular stimulation will develop faster than those who receive less or no stimulation at all. The brain tissue of children who receive a lot of stimulation will develop to 80% by the age of 3 years. If the child is never given stimulation, the brain tissue will decrease, this has a tendency to reduce the quality of human resources in the future. Stimulation of infant/toddler growth and development using the Pre-Screening Questionnaire for Development (KPSP) is one of the stimulation methods that can be used to detect toddler growth and development. Therefore, it is very important to improve the skills of Posyandu Cadres in using KPSP. The output from the use of KPSP will be one of the indicators of the success of fostering toddler growth and development at Posyandu, not only improving the health and nutritional status of toddlers but also the mental, emotional, social and independence of toddlers developing optimally.